Review of Political Ethics and Sadd adz-Dzari'ah on the Phenomenon of Political Dynasties in Indonesia - Lucky Andrie Awan (al-Afkar, Journal For Islamic Studies, 2026)
This study examines the issue of political dynasties in Indonesia. The background to this issue is concern over the significant rise in political dynasty practices, as evidenced by the increase in the number of regional election candidates from political elite families. Specifically, this study discusses: 1) How regulations in Indonesia govern the issue of political dynasties, 2) How political ethics assess the phenomenon of political dynasties, and 3) How sadd adz-dzari'ah assesses the phenomenon of political dynasties. This study uses qualitative methods with data collection techniques from books, journals, and previous studies. The main results show that political dynasties arise due to imperfect regulations and their implementation. From the perspective of Kantian political ethics, this practice is morally unjustifiable because it violates the three main principles of Kantian political ethics. Meanwhile, from the perspective of sadd adz-dzari'ah, appropriate efforts are needed from the government, because political dynasties can threaten the principles of democracy in Indonesia.